Effects of Four Lipid Metabolism-Related Polymorphisms on Body Composition Improvements After 12 Weeks of High-Intensity Interval Training and Dietary Energy Restriction in Overweight/Obese Adult Women: A Pilot Study - Andrade-Mayorga, Omar; Díaz, Erik; Salazar, Luis A. (Frontiers in Physiology, 2021)
Background: Polymorphisms in lipid metabolism-related genes have been associated with obesity and body composition, but these have been scarcely described concerning the magnitude of the response to exercise interventions in the overweight/obese population. Objective: To evaluate the association of PLIN1 (rs1052700 and rs2304795), LPL (rs283), ADRB3 (rs4994) polymorphisms with high and low responders to fat mass reduction after 12 weeks of high-intensity interval training (HIIT) and dietary energy restriction in overweight/obese adult women. In addition, we examined the effect of these genetic variants on body composition changes. Methods: Forty-three unrelated overweight/obese adult women were incorporated and genotyped, of which 30 women (age= 27.4 ± 7.9 years; BMI= 29.9 ± 3.3 kg/m2) successfully completed the 12-week supervised HIIT program plus an individually prescribed home hypocaloric diet. Results: An association was observed between the PLIN1 rs1052700 polymorphism with high and low responders (χ2=8.138; 2 df; P=0.01). Moreover, after the intervention, the carriers of TT genotype of PLIN1 rs1052700 as compared to AA and AT showed a greater reduction in absolute fat mass (Δ: - 5.1 ± 1.8 vs. -1.8 ± 1.4 vs. -2.1 ± 2.3 kg; P=0.04). The effect size of this fat mass reduction between TT and AT genotypes was a mean difference of -3.01 kg [95%IC -4.88 – -1.1], and between TT and AA genotypes was -3.29 kg [95%IC -4.86 – -1.65]. No differences were observed for other polymorphisms investigated. Conclusion: These results suggest that the rs1052700 (14995A>T) polymorphism of the PLIN1 gene is associated with a differential response to fat mass reduction after a 12-week intervention in overweight/obese adult women. In addition, women with the TT genotype of this genetic variant showed greater changes in fat mass than AA and AT genotypes. However, further studies are needed to confirm these findings.